1996
DOI: 10.1021/jp961140r
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Nitrous Acid (HONO) in Sulfuric Acid Solutions

Abstract: The Henry's law solubility of nitrous acid (HONO) has been studied in sulfuric acid solutions as a function of acid concentration in the range 0.3-73.6 wt % and temperature between 248 and 298 K by measuring the distribution of HONO between the gas and liquid phases using a bubbler-type gas-liquid reactor. Gas phase concentrations have been measured by highly sensitive tunable diode laser spectrometry, whereas the liquid phase has been analyzed by ion chromatography. At 298 K the Henry's law constant of HONO i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
63
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 26 publications
14
63
0
Order By: Relevance
“…The solubility of HNO 2 in water has been directly measured by Park and Lee (1988). Their data are also in line with the extrapolated solubility from those by Becker et al (1996), who measured the solubility as a function of sulphuric acid composition (0.3 wt % and above). The preferred expression is consistent with that presented in data sheet VI.A4.7 for 0 wt % H 2 SO 4 and agrees well with the temperature dependence measured by Park and Lee.…”
Section: Comments On Preferred Valuessupporting
confidence: 68%
See 2 more Smart Citations
“…The solubility of HNO 2 in water has been directly measured by Park and Lee (1988). Their data are also in line with the extrapolated solubility from those by Becker et al (1996), who measured the solubility as a function of sulphuric acid composition (0.3 wt % and above). The preferred expression is consistent with that presented in data sheet VI.A4.7 for 0 wt % H 2 SO 4 and agrees well with the temperature dependence measured by Park and Lee.…”
Section: Comments On Preferred Valuessupporting
confidence: 68%
“…The available studies determining the effective solubility of HNO 2 directly by Becker et al (1996), Longfellow et al (1998) and Baker et al (1999) agree very well as far as they overlap in composition and temperature. We recommend using an expression based on a parameterisation proposed by Becker et al (1996):…”
Section: Comments On Preferred Valuesmentioning
confidence: 58%
See 1 more Smart Citation
“…Due to its lack of solubility in water, loss of 222 Rn from the atmosphere is solely by radioactive decay (through a number of shortlived daughters) to 210 Pb with a half-life of 3.8 days. Lelieveld and Crutzen (1991); (5) Hanson et al (1992); (6) O'Sullivan et al (1996); (7) Staudinger and Roberts (2001); and (8) Becker et al (1996). Two additional tracers were included in the HadGEM2-UKCA coupled simulation.…”
Section: Convective Transport and Boundary Layer Mixingmentioning
confidence: 99%
“…But Saastad et al [1993] showed that the heterogeneous HONO formation mechanisms proposed by Burley and Johnston [1992], involving NO and NO2, were not efficient. Also, laboratory studies have shown that HONO, while soluble, will not be present in stratospheric aerosols at the concentrations necessary for NSA N20 precipitation [Becker et al, 1996;Longfellow et al, 1998]. CH4 Therefore, NSA formation has generally been discounted.…”
Section: Introductionmentioning
confidence: 99%